Digitalization as a Tool to Increase Productivity Efficiency - Shukhrat Erkinjovich Otajonov; Muzaffar Ummatovich Kurbanov (Research Parks Publishing LLC, 2021)
The article is devoted to the analysis of opportunities to increase production efficiency, which opens up in the framework of strategic planning at the state and enterprise level of the digital economy. The article discusses concepts such as digital economy, development strategy, production efficiency, competitive advantages. The importance of a careful approach to the development of key performance indicators of the enterprise was emphasized. As a result, the need for a strategic approach to the implementation of digital economy tools is being put forward.